Effects of Aspirin on Odontogenesis of Human Dental Pulp Cells and TGF-β1 Liberation from Dentin In Vitro - V. Khampatee; C. Zhang; L. Chou (Hindawi Limited, 2022)
Aim. This in vitro study aimed to investigate the roles of aspirin (ASA) and its concentrations on the odontogenesis of human dental pulp cells (HDPCs) and to investigate the influence of ASA on TGF-β1 liberation from dentin. Methodology. HDPCs were cultured in a culture medium with 25, 50, 75, 100, and 200 μ·g/mL ASA and 0 μ·g/mL ASA as a control. The mitochondrial activity of HDPCs was assessed using an MTT assay. Crystal violet staining and triton were used to evaluate cell proliferation rates. ALP activity was measured with a fluorometric assay. Expressions of DSP and RUNX2 were determined with the ELISA. DSP and RUNX2 mRNA levels were measured with RT-qPCR. Alizarin red staining was conducted to evaluate the mineralized nodule formation. Dentin slices were submerged in PBS (negative control), 17% EDTA (positive control), and ASA before collecting the solution for TGF-β1 quantification by the ELISA. The data were analyzed by the t-tests and ANOVA, followed by the Tukey post hoc tests. P values < 0.05 were considered statistically significant. Results. The results showed that 25-50 μ·g/mL ASA promoted mitochondrial activity of HDPCs at 72 h (P<0.05) and yielded significantly higher proliferation rates of HDPCs than the control at 14d and 21d (P<0.001). All concentrations of ASA promoted odontogenic differentiation of HDPCs by enhancing the levels of DSP and RUNX2, their mRNA expression, and mineralization in a dose-dependent manner. Also, ASA yielded significantly higher TGF-β1 liberation after conditioning dentin for 5 min (25, 200 μ·g/mL; P<0.001) and 10 min (200 μ·g/mL; P<0.05). Conclusions. This in vitro study demonstrated that ASA, especially in high concentrations, promoted the odontogenesis of HDPCs and TGF-β1 liberation from dentin, showing the potential of being incorporated into the novel pulp capping materials for dental tissue regeneration.